A NIR fluorescent probe tracing norepinephrine exocytosis and depression occurrence at the cellular level. Issue 18 (11th February 2022) - Zhou, Na; Yin, Caixia; Yue, Yongkang; Zhang, Yongbin; Cheng, Fangqin; Huo, Fangjun
Abstract : A NIR fluorescent probe tracing norepinephrine exocytosis and depression occurrence at the cellular level revealed that norepinephrine exocytosis rather than the inherent intracellular concentration was related with depression. Abstract : A NIR fluorescent probe tracing norepinephrine exocytosis and depression occurrence at the cellular level revealed that norepinephrine exocytosis rather than the inherent intracellular concentration was related with depression.